Surgical Robotics 2018
DOI: 10.5772/intechopen.71164
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Hiatal Hernia Repair

Abstract: Robotic surgery has revolutionized medicine during the last 16 years by transformation of the classic operating theaters into computer-mediated working stations. Numerous procedures have been proved to be feasible and safe by using the continuously evolving, various robotic platforms. From the early beginnings of this revolution, challenging operations such as those concerning the gastroesophageal junction, especially in super-obese patients or during redo operations, proved out to have certain beneits when pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In adults use of a suture to suspend the appendix has been suggested by Roberts et al [7]. Other authors have suggested single port appendectomy [10–12] and transvaginal appendectomy [13, 14], and even robotic assisted appendectomy has been done [15]. In the rural setting with limited resources and staff available, reduction of individuals involved in the procedure is desired.…”
Section: Introductionmentioning
confidence: 99%
“…In adults use of a suture to suspend the appendix has been suggested by Roberts et al [7]. Other authors have suggested single port appendectomy [10–12] and transvaginal appendectomy [13, 14], and even robotic assisted appendectomy has been done [15]. In the rural setting with limited resources and staff available, reduction of individuals involved in the procedure is desired.…”
Section: Introductionmentioning
confidence: 99%